Electronic Structures and NLO Properties of a Series of TMDs Lateral‐Core–Shell Heterostructures Quantum Dots. Issue 4 (3rd February 2023) - Li, Danting; Wei, Yadong; Hu, Yangyang; Zhang, Guiling; Li, Weiqi; Yang, JianQun; Li, XingJi; Tian, Wei Quan
Abstract: The electronic structures and nonlinear optical (NLO) responses of eight triangle group‐VI transition metal dichalcogenides (TMDs) lateral‐core–shell heterostructures quantum dots (QDs) [MaX2 MbX2 and MXa2 MXb2 ; M (Ma, Mb) = Mo and W; X (Xa, Xb) = S and Se] have been explored by using quantum chemistry method. Frontier molecular orbital (FMOs) analyses indicate that the triangular frameworks with more active W and/or Se atoms at shell have smaller energy gaps than those with Mo and/or S atoms, and the active sites of the ultra‐small TMD heterostructures mainly locate at the edge and/or the corner of the frameworks. Generally speaking, active atoms at the shell are beneficial to the enhancement of the frequency‐dependent first hyperpolarizabilities compared with the active atoms in the cores. First hyperpolarizability density analyses show that the local contributions of the first hyperpolarizability in x direction is mainly located at the left and right corners, while that in y direction is mainly located at the bottom edge and top corner, confirming the important role that the shell of the TMDs lateral‐core–shell heterostructure QDs play in its NLO response. Further, the electronic transitions contributed to the SHG responses also occur at the shell of these triangular frameworks. Abstract : The electronic structures and nonlinear optical (NLO) responses of the transition metal dichalcogenides (TMDs) lateral‐core–shell heterostructures quantum dots (QDs) have been explored using quantum chemistry method. Active sites of the triangular frameworks mainly locate at the shell. Active atoms at the shell are beneficial to the enhancement of the NLO responses.